The Urgency of Regulating the Transparency Principle of the 'AI System' in Indonesia: The Phenomenon of Self-Preferencing and Regulation in the European Union - Ratih Mulia Fazriati; Sinta Dewi Rosadi; Prita Amalia (Dinasti Research, 2025)
This research discusses the phenomenon of self-preferencing by artificial intelligence (AI) technology in the e-commerce sector in Indonesia, as well as a comparison with regulations in the European Union. AI as an automated decision-making tool has been adopted by e-commerce platforms to improve efficiency and service personalization. However, some e-commerce platforms use AI for self-preferencing practices, such as Shopee's practice with SPX couriers. This practice raises issues of unfair business competition and threatens the transparency principle of technology utilization. This research analyzes relevant regulations such as UU ITE, PP PSE, and PP E-Commerce by conducting a comparative study of regulations in the European Union such as the Artificial Intelligence Act, Digital Market Act, and P2B Regulation. This research shows that AI is constructed as an electronic agent whose utilization must be in line with the principles contained in the ITE Law. In the ITE Law, the principle of transparency for electronic agents is not regulated. This is different from regulations in the European Union which regulate the principle of transparency as a form of legal certainty for business actors in the e-commerce platforms.